2016
DOI: 10.5114/pg.2016.57819
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary prevention of colorectal cancer in the Czech Republic

Abstract: Colorectal cancer is one of the most frequent malignancies in the Czech Republic and worldwide. Also, a high prevalence of overweight and obesity, a high proportion of smokers in the population, and one of the highest per capita alcohol consumption rates are typical for the Czech population. The role of general practitioners in the prevention of colorectal cancer is crucial. In primary prevention, the doctor should emphasise the importance of a healthy lifestyle – a balanced diet rich in fruits and vegetables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the Czech Republic, a European country with CRC incidence among the highest worldwide, only 25% of individuals eligible for screening undergo regular screening: ∼500 000 immunologic fecal occult blood tests (IFBTs) a year 2. However, in a study that included 50 primary healthcare centers in Serbia, 50 894 individuals were invited to participate in a CRC screening program using IFBT.…”
Section: Participation Rates Of Colorectal Cancer Screening Programsmentioning
confidence: 99%
“…In the Czech Republic, a European country with CRC incidence among the highest worldwide, only 25% of individuals eligible for screening undergo regular screening: ∼500 000 immunologic fecal occult blood tests (IFBTs) a year 2. However, in a study that included 50 primary healthcare centers in Serbia, 50 894 individuals were invited to participate in a CRC screening program using IFBT.…”
Section: Participation Rates Of Colorectal Cancer Screening Programsmentioning
confidence: 99%
“…In contrast with consistent result which con rmed an inverse association between physical activity and colon cancer risk [9,23,31,[96][97][98][99][100][101][102][103][104][105][106][107], results from the studies that examined the association between physical activity and rectal cancer risk are inconsistent [6,22,23,74,76,78,96,97,103,108,109]. However, Colinda C. J. M. Simons et al, in a casecontrol study carried out on 120 000 subjects in Netherland found that regular participation in recreational physical activity such as daily walking and riding bicycle reduced rectal cancer risk among women but not among men [110].…”
Section: Colorectal Cancermentioning
confidence: 62%
“…A limitation of our study is the absence of sufficient dietary data in both the cohorts (none in the Irish and substantial missing and/or rudimentary data in the Czechs). However, Irish and Czech populations present similar dietary and lifestyle patterns, rich in processed and red meat, lacking in fruit and vegetable intake, and high smoking and alcohol consumption rates [45,46]. Furthermore, the incidence of excess weight and obesity is constantly growing in both countries [47,48].…”
Section: Discussionmentioning
confidence: 99%